Developing heuristic and meta-heuristic algorithms for the problem of joint order batching and collector routing in single and multiple-cross-aisle warehouses - Zahra Shamlou; Taha Keshavarz (تصمیم گیری و تحقیق در عملیات)
Purpose: Organization of the order selection process is one of the most important issues in warehouse management, and combining several customer orders in one order can increase the efficiency of warehouse operations and better use of resources and labor. It also reduces the time of the order selection process and the distance traveled.Methodology: In this research, we have presented a method to solve the problem of order batching and collectors routing. A meta-heuristic based on the genetic algorithm is proposed in this research. For a more accurate comparison, in addition to the category number of common items, we also considered the percentage of common items in each order.Findings: The proposed method in this research has been compared with the combination of Nearest Neighbor (NN), Largest Gap, and S-shape algorithms. The test results on the random data sets have shown that the genetic algorithm provides fast and effective solutions. By evaluating the sensitivity analysis of the parameters, it was observed that the distance covered by the combined genetic method is better than the S-shape+Largest Gap+NN method.Originality/Value: In this article, the genetic algorithm is used for the problem of classification of joint orders and routing of collectors in warehouses at the same time.